Active following (engagement) of fiction series on the internet. Attention and emotion as triggers of the binge-watching - Arrojo, María José (2019)
The research focuses on how new communicative designs in the digital environment influence the perception and engagement of communicative content. The study proposes two main objectives: 1) analyze how the support itself (telephone, computer, television) conditions the perception and engagement of fiction series; and 2) how these technological supports can condition the consumption. To carry out the research, the fiction "The 100" was chosen, and the differences in perception were analyzed according to the distribution channel –subject to a schedule or not– and the impact of the level of consumption according to the technological support used. The scientific method employed is the Neuromarketing Research Methodology applied to the study of communicative phenomena. The results corroborate the hypothesis that the support and the transmission device condition both the level of attention and the active follow-up (engagement) that is developed with the audiovisual content.